MENGUJI LITERASI KEUANGAN, GAYA HIDUP DAN PENGENDALIAN DIRI TERHADAP PERILAKU KONSUMTIF MILLENIAL PENGGUNA GO-JEK SUKOHARJO - Rafika Putri Pratiwi; Ari Susanti (JURNAL LENTERA BISNIS, 2022)
This research intends to find the effect of Financial Literacy, Lifestyle and Self-Control on Millennial Consumptive Behavior of Go-Jek Users in Sukoharjo Regency. Purposive sampling is a sampling technique carried out in this study based on certain characteristics that have a relationship with population characteristics. In this study, the population and sample were based on the following criteria: the millennial generation born in 1980-2000 and at least 2 users of the Go-Jek application. A total of 125 respondents are the samples used in this study. The analysis used is multiple regression test using the SPSS program. Based on this study, the results showed that: (1) Financial literacy had no significant effect on consumptive behavior, (2) Lifestyle had a significant effect on consumptive behavior, (3) Self-control had an effect on consumptive behavior.Key words: Financial Literacy, Lifestyle, Self-Control and Comsumptive Behavior